Volume 7A: Structures and Dynamics 2016
DOI: 10.1115/gt2016-57230
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Damping Potential of Strip Damper on a Real Turbine Blade

Abstract: This paper investigates the damping potential of strip dampers on a real turbine bladed disk. A 3D numerical friction contact model is used to compute the contact forces by means of the Alternate Frequency Time domain method. The Jacobian matrix required during the iterative solution is computed in parallel with the contact forces, by a quasi-analytical method. A finite element model of the strip dampers, that allows for an accurate description of their dynamic properties, is included in the steady-state force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Dry friction can be incorporated into the blade design, in the form of shrouds, lacing wires or zigzag pins. Alternatively, external devices such as solid dampers (available in several designs, cylindrical, curved flat, wedge damper, etc), thinstrip dampers [3,4] or ring dampers [5,6] of the different sources of damping in turbo engines was performed in [2]. It was shown that the values of Q (amplitude factor, inverse of the loss factor η) may vary as follows: 3000 to 10,000 for material damping, 50 to 140 for root damping, 180 to 2500 for shroud damping, and 15 to 250 for platform damping (external dry friction dampers).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dry friction can be incorporated into the blade design, in the form of shrouds, lacing wires or zigzag pins. Alternatively, external devices such as solid dampers (available in several designs, cylindrical, curved flat, wedge damper, etc), thinstrip dampers [3,4] or ring dampers [5,6] of the different sources of damping in turbo engines was performed in [2]. It was shown that the values of Q (amplitude factor, inverse of the loss factor η) may vary as follows: 3000 to 10,000 for material damping, 50 to 140 for root damping, 180 to 2500 for shroud damping, and 15 to 250 for platform damping (external dry friction dampers).…”
Section: Introductionmentioning
confidence: 99%
“…The design of the strips, not only for sealing but also for damping purpose, represents a topic of recent interest for the turbine designers, as very few studies can be found in literature [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the proposed calculation methodologies for bulk UPDs use simplifying assumptions, such as neglecting the damper inertia or flexibility [11,19,25]. However, these assumptions, perfectly adequate for solid UPDs, cannot be applied to model strip dampers, as they are highly flexible and consequently their flexible vibrational modes need to be taken into account in the modelling process through FE modelling [17].…”
Section: Introductionmentioning
confidence: 99%
“…In this way the strips act both as friction dampers and as an additional constraint affecting the blade natural frequencies. The design of the strips, not only for sealing, but also for damping purpose, represents a topic of recent interest for the turbine designers, as very few studies can be found in literature [4,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation